Correlation between clinical severity and extent of autonomic cardiovascular impairment in the acute phase of subarachnoid hemorrhage - Borutta, Matthias; Gerner, Stefan T.; Möser, Philip; Hölter, Philip; Engelhorn, Tobias; Dörfler, Arnd; Huttner, Hagen B.; Schwab, Stefan; Kuramatsu, Joji; Köhn, Julia (Journal of Neurology, 2022)
Background and aim: To assess associations between clinical severity and possible dysfunction of autonomic cardiovascular modulation within the acute phase after spontaneous subarachnoid hemorrhage (SAH). Methods: In this prospective observational study, in 51 patients with spontaneous SAH, Hunt-and-Hess scores (H&H) were assessed and cardiovascular autonomic modulation was monitored within 24 h after SAH-onset. From 5 min time-series of R–R-intervals (RRI) and blood-pressure (BP) recordings, we calculated autonomic parameters including time-domain [RRI-coefficient-of-variation (RRI-CV) and square-root-of-the-mean-squared-differences-of-successive-RRIs (RMSSD)] and frequency-domain parameters [low- and high-frequency-powers of RRI- and BP-modulation (RRI-LF-, RRI-HF-, SBP-LF-powers) and RRI-total-powers]. Data were compared to those of 20 healthy volunteers. Results: RRI- and BP-values did not differ between groups. Yet, parameters of sympathetic (RRI-LF-powers 141.0 (18.9–402.4) ms2 vs 442.3 (246.8–921.2) ms2, p = 0.001) and total autonomic modulation (RRI-CV 2.4 (1.2–3.7) ms2 vs 3.7 (3.1–5.3) ms2, p = 0.001) were significantly lower in patients than in controls. Subgroup analyses (patients with H&H < 3 vs H&H ≥ 3) and Spearman-rank-correlations revealed increasing loss of sympathetic (RRI-LF-powers 338.6 (179.7–710.4) ms2 vs 72.1 (10.1–175.9) ms2, p = 0.001, rho = − 0.524) and total autonomic modulation (RRI-CV 3.5 (2.3–5.4) ms2 vs 1.6 (1.0–2.8) ms2, p < 0.001, rho = − 0.519) with higher H&H-scores. Multiple-logistic-regression underlined the significant influence of H&H-scores on sympathetic (RRI-LF-powers, p = 0.033) and total autonomic modulation (RRI-CV, p = 0.040) compared to possible confounders (e.g., age, intubation). Conclusion: Within the acute phase, spontaneous SAH induces a decrease in sympathetic and total autonomic cardiovascular modulation. Higher H&H-scores were associated with increasing autonomic dysfunction and may therefore augment the risk of cardiovascular complications and poor clinical outcome.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Autonomic nervous system; Heart rate variability; Hunt and Hess; Subarachnoid hemorrhage